2015
DOI: 10.1161/circulationaha.114.011079
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 4 Induces Cardiac Fibrosis and Hypertrophy Through Activating Akt/mTOR and NFκB Signaling Pathways

Abstract: Background NADPH oxidase 4 (Nox4) has been implicated in cardiac remodeling, but its precise role in cardiac injury remains controversial. Furthermore, little is known about the downstream effector signaling pathways activated by Nox4-derived ROS in the myocardium. We investigated the role of Nox4 and Nox4 associated signaling pathways in the development of cardiac remodeling. Methods and Results Cardiac-specific human Nox4 transgenic mice (c-hNox4Tg) were generated. Four groups of mice were studied: 1) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
148
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(158 citation statements)
references
References 56 publications
9
148
1
Order By: Relevance
“…A recent study, albeit in the heart, supports our findings that NOX4 plays a role in fibrosis and hypertrophy [34]. In that study, NOX4 was shown to induce cardiac fibrosis and hypertrophy via activation of the Akt/mTOR and nuclear factor-κB signalling pathways [34].…”
Section: Discussionsupporting
confidence: 79%
“…A recent study, albeit in the heart, supports our findings that NOX4 plays a role in fibrosis and hypertrophy [34]. In that study, NOX4 was shown to induce cardiac fibrosis and hypertrophy via activation of the Akt/mTOR and nuclear factor-κB signalling pathways [34].…”
Section: Discussionsupporting
confidence: 79%
“…Our current study cannot exclude the possibility that plumbagin attenuates IL-1β secretion partly by inhibiting NF-κB activation, which is required for increased PKM2 expression in epidermal growth factor-induced glycolysis in cancer cells (44). Furthermore, NOX4 is required for activation of NF-κB in response to hypoxia and LPS (45,46). It is possible that the NOX4-mediated PKM2 expression may depend on the activation of NF-κB in LPS-induced macrophages.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies demonstrated that the phosphatidyl inositol 3‐kinase–Akt signaling pathway protects the heart against injuries and is therefore called a survival factor for cardiomyocytes; however, this pathway also induces cardiac hypertrophy (Fujio et al ., 2000; Condorelli et al ., 2002; Zhao et al ., 2015). Our previous study demonstrated that EETs and CYP epoxygenases markedly activate Akt and inhibit cardiac hypertrophy (Xiao et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%